Government in the Perspective of Fiqh Siyasah: A Critical Study between Democracy and the Concept of Caliphate - Muhammad Ikhlas Bin Rosele lubis; Mhd Soleh Hasibuan; Adinda Putri Hutabarat (Jurnal Cendikia ISNU SU, 2025)
This study discusses the perspective of Islamic jurisprudence on the system of government, especially in comparing the concepts of democracy and the caliphate. In Islamic history, the caliphate was seen as an ideal system of government that applied Islamic sharia comprehensively, while democracy was a modern system rooted in the sovereignty of the people and individual freedom. This research uses the library research method by analyzing classical and contemporary sources, both from fiqh literature and Islamic political thought. The results of the study show that there is a diversity of opinions among scholars regarding the validity of democracy in Islam. Some scholars accept democracy as a means of ijtihadiyah that can be adapted as long as it does not contradict the basic principles of sharia. Meanwhile, the caliphate system is seen as more ideal normatively, but it faces challenges in contextual implementation in the modern era. This study concludes that the fiqh approach to the system of government is dynamic and contextual, and opens up space for the integration of Islamic values in various forms of political systems.